ANALISIS TINGKAT KESEHATAN KOPERASI CREDIT UNION MAMBUIN TEMPAT PELAYANAN PRAFI KABUPATEN MANOKWARI - Cinthia Rianita Tumbio; Sarah Usman; Ted M Suruan (Universitas Malikussaleh, 2022)
This study aims to determine the level of health of the Mambuin Credit Union Cooperative TP Prafi Manokwari Regency in 2014-2018 based on the Regulation of the Minister of Cooperatives and SMEs Number: 14 / Per / M.KUKM / XII / 2009 concerning aspects of capital, aspects of productive asset quality, aspects efficiency, aspects of liquidity, aspects of independence and growth, aspects of cooperative identity and management aspects. In this study data were collected through observation, documentation and interview methods. Data were analyzed using qualitative and quantitative techniques guided by the Regulation of the Minister of Cooperatives and SMEs Number: 14 / Per / M.KUKM / XII / 2009. The results showed that the health level of the 2014 Prafi Credit Union Cooperative in the 2014-2018 category was